Rural Settlement Development and Environment Carrying Capacity Changes in Progo River Basin - Su Ritohardoyo; P Priyono (Universitas Muhammadiyah Surakarta, 2005)
Generally the broader rural settlement the heavier population pressure on agricultural land. It indicates that carrying capacity of the rural environment threatened lower. The spatial distribution of the threat in a river basin is quite important as one of the river basin management inputs. Therefore, this article aims at exposing result of research about influence rural population growth and rural settlement land changes to environment carrying capacity. This research was carried out in the rural area in Progo river basin consists 56 sub districts (34 sub districts part of Jawa Tengah Province, and 22 sub districts part of Yogyakarta Special Region). The whole sub districts are such as unit analysis, and research method is based on secondary data analysis. Several data consist Districts Region in Figure 1997 and 2003 (Temanggung, Magelang, Kulon Progo, Sleman and Bantul) such as secondary data analysis. Data analysis employs of frequency and cross tabulation, statistics of regression and test. Result of the research shows that population growth of the rural areas in Progo river basin are about 0.72% annum; or the household growth about 3.15% annum as long as five years (1996-2003). Spatial distribution of the population growth in the upper part of the Progo river basin is higher than in the middle and lower part of the basin. The number proportion of farmer in every sub district area in this river basin have increased from 69.95% in 1997 to 70.81% in the year of 2003. It means that work opportunities broadening are still sluggish. However, the number proportion of farmers in the upper part of the Progo river basin is lower than in the middle and lower part of the basin. The rates of settlement land areas changes (0.32 ha/annum) as long as five years (1997-2003) is not as fast as the rates of agricultural land areas changes (0.47 ha/annum). Spatial land settlement areas changes in the lower (6.1 ha/annum) and middle parts (2.4 ha/annum) faster than upper part of the river basin, as a consequence the different accessibility to urban area. Environment carrying capacity of every sub district areas in this river basin becomes lower as long as five years (1997-2003). In the upper part of the basin however, the index of environment carrying data (0.13) higher than in the lower part of this river basin (0.09), especially in the several sub districts surrounding urban area. The environment carrying capacity of Progo river basin depends on the land settlement and the growth of household number changes. However, influence of the land settlement area changes is stronger than the growth of household number changes to the environment carrying capacity. This result of research shows that spatial and temporal characteristics of settlement environment degradation in the lower and middle parts wider than in the upper part of Progo river basin in the coming twenty five of years.